Strawberry growth under levels of salinity and organic fertilization - Sousa, Geocleber Gomes de; Souza, Maria Vanessa Pires de; Guilherme, José Marcelo da Silva; Silva Junior, Francisco Barroso da; Freitas, Ana Gabriela Sousa; Viana, Thales Vinicius de Araújo (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The objective was to evaluate the initial growth of strawberry under irrigation with saline water in a soil with and without biofertilizer. The experiment was conducted in a protected environment at the Experimental Station, Agrarian Sciences of the Federal University of Ceará, Fortaleza, during the period of September and October of 2016. The experimental design was a completely randomized following the 5 x 2 factorial scheme, with five replications. The first treatment was constituted by the levels of electrical conductivity of irrigation water, being: 0.5 dS m-1; 1.0 dS m-1; 1.5 dS m-1; 2.0 dS m-1 e 2.5 dS m-1, and the second treatment comprised two conditions: with and without biofertilizer. The following variables were evaluated: number of leaves, root length, shoot dry matter, root and total and electrical conductivity. Irrigation water salinity affected the number of leaves, leaf area, root length, shoot, root and total dry mass, but with lower intensity in soil with bovine biofertilizer, demonstrating that the input attenuates the effects of salinity on strawberry growth.